2015
DOI: 10.1111/1750-3841.13076
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structural Characteristics of Polysaccharide Fractions from Canarium album (Lour.) Raeusch and Their Antioxidant Activities

Abstract: The molecular structural characteristics, antioxidant activities, and structure-function relationships of polysaccharide fractions from Canarium album were first investigated in this study. The results provided background and practical knowledge for the deep-processed products of C. album with high added value. CPS2 was the major antioxidant component of CPS, which could be exploited as a valued antioxidant ingredient in food and pharmaceutical industries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Some researchers have reported that polysaccharides with lower molecular weights present stronger reducing power [ 5 , 45 ], but Huang et al reported that polysaccharides with larger molecular weights possessed higher reducing power [ 46 ]. In the present work, the results indicated that there was no obvious relationship between molecular weight and antioxidant activity, which was also consistent with reported results [ 47 , 48 ]. Uronic acids are usually considered as a key factor in antioxidant activity.…”
Section: Resultssupporting
confidence: 93%
“…Some researchers have reported that polysaccharides with lower molecular weights present stronger reducing power [ 5 , 45 ], but Huang et al reported that polysaccharides with larger molecular weights possessed higher reducing power [ 46 ]. In the present work, the results indicated that there was no obvious relationship between molecular weight and antioxidant activity, which was also consistent with reported results [ 47 , 48 ]. Uronic acids are usually considered as a key factor in antioxidant activity.…”
Section: Resultssupporting
confidence: 93%
“…Polydispersity, expressed as Mw/Mn, appraised the molar mass distribution of a polymer, the value of which increased with the widening of molar mass distribution. 34 Thus, we deduced that RP had a relatively narrow molar mass distribution, with Mw/Mn = 1.515. In addition, the z-average root meant the square radius of gyration (Rz) of RP was 51.1.…”
Section: Molecular Weight Determinationmentioning
confidence: 89%
“…In vitro experiments confirmed that Atractylodes lancea volatile oils could inhibit the growth of H. pylori , reduce the biofilm formation, and decrease the translocation of Cag A, indicating that the volatile oil of Atractylodes Rhizoma is a potential inhibitor of H. pylori [ 34 ]. Canarium album Raeusch, belonging to the Burseraceae family, has numerous biological activities, including anti-inflammatory, antioxidative, and antiviral effects [ 76 , 77 ]. An in vitro experiment showed that Canarium album Raeusch fruit extracts inhibited H. pylori by suppressing growth, destroying the bacterial structure, and down-regulating the virulence factors [ 35 ].…”
Section: Pharmacological Mechanisms Of Tcm For the Treatment Of Cgmentioning
confidence: 99%